WAYS TO INCREASE THE INCOME OF THE POPULATION DURING ECONOMIC TRANSFORMATION - Qulmatova D.Kh, (TADQIQOTLAR, 2025)
Abstract:  This  article  analyzes  effective  ways  to  increase  the  income  of  the population during economic transformation processes. It discusses key factors such as raising  employment  levels,  encouraging  entrepreneurship,  introducing  modern technologies, improving the investment climate, and developing vocational education. The article also reviews best practices from around the world, including the experience of Uzbekistan. Concrete proposals and recommendations are provided for diversifying sources of income and expanding social protection programs for the population.